SMALL BUSINESS LENDING IS THE KEY TO THE COUNTRY'S DEVELOPMENT (American Journal of Business Management, Economics and Banking, 2025)
Lending to small businesses and private entrepreneurship plays an important role in GDP growth and in the development of the country's economy. Crediting small business and private business plays main role in increasing GDP and developing economy of the country.